Influence of hepes on in vitro maturation of canine oocytes in different stages of the estrous cycle - Pereira, Leda Maria Costa [UNESP]; Bersano, Paulo Ricardo Oliveira; Lopes, Maria Denise [UNESP] (FapUNIFESP (SciELO), 2019)
Unlike other domestic animals, in vitro maturation (IVM) of canine oocytes still has limited success. The aim of this study was to evaluate the effect of HEPES on the in vitro maturation of dog oocytes in anestrus and diestrus. Ovaries were collected, aseptically isolated and transported refrigerated at a temperature of 4°C. Cumulus-oocyte complexe (COCs) from the two phases of estrous cycle were subjected to two treatments: medium TCM-199 with addition of 25 mM HEPES (TG) and medium without supplementation (CG). After 72 h of maturation, COCs were denuded, fixed and stained with Hoechst 33342 to assess nuclear maturation. The oocytes obtained from the anestrus and diestrus phases of the TG showed a higher frequency of oocytes in metaphase II (M-II) (p < 0.01) stage. Comparing the different reproductive status, it was observed that the oocytes obtained from the diestrus phase presented higher rates of GVBD (germinal vesicle breakdown) and M-II. Our results showed that HEPES preserves the viability and oocyte morphology essential for the acquisition of meiotic competence, increasing the M-II rates and that the oocytes obtained from the diestrus phase are better able to complete oocyte maturation.
Influência do hepes na maturação in vitro de oócitos caninos obtidos de cadelas em diestro e anestro
Keywords: Biotechniques; Bitches; Culture medium; Estrous cycle; Meiotic competence